2001
DOI: 10.1016/s0960-9822(01)00526-7
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans clk-2, a gene that limits life span, encodes a telomere length regulator similar to yeast telomere binding protein Tel2p

Abstract: An important quest in modern biology is to identify genes involved in aging. Model organisms such as the nematode Caenorhabditis elegans are particularly useful in this regard. The C. elegans genome has been sequenced [1], and single gene mutations that extend adult life span have been identified [2]. Among these longevity-controlling loci are four apparently unrelated genes that belong to the clk family. In mammals, telomere length and structure can influence cellular, and possibly organismal, aging. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Of the C. elegans genes identified so far whose mutations make worms live longer, only one gene, clk-2, was reported to affect telomere length, with some controversy [20][21][22] . It would be difficult to determine whether long telomeres extend lifespan in these worms, because the clk-2 mutation causes many other pleiotropic effects, such as a defective DNA checkpoint function and slow metabolism 23 that induces stress resistance in the soma.…”
mentioning
confidence: 99%
“…Of the C. elegans genes identified so far whose mutations make worms live longer, only one gene, clk-2, was reported to affect telomere length, with some controversy [20][21][22] . It would be difficult to determine whether long telomeres extend lifespan in these worms, because the clk-2 mutation causes many other pleiotropic effects, such as a defective DNA checkpoint function and slow metabolism 23 that induces stress resistance in the soma.…”
mentioning
confidence: 99%
“…On the other hand, S. pombe Tel2 apparently does not play a critical role in telomere length control, because Tel2 repression did not show any changes in telomere length (data not shown). In C. elegans, rad-5 and clk-2 mutations have little effect on telomere length (41), whereas other reports argued that clear changes in telomere length (both longer and shorter) are observed in clk-2 mutants (42,43). In humans, overexpression of CLK2 gradually lengthens telomere DNA (45), but the effect of inactivation of CLK2 on telomere length is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In Caenorhabditis elegans, the rad-5 mutant was isolated as a radiationsensitive mutant showing high sensitivity to UV and x-ray irradiation (38), and the clk-2 mutant was isolated as a viable maternal-effect mutant showing alteration of the timing of some developmental and behavioral events, including the embryonic cell cycle and life span (39,40). Ahmed et al (41) showed that rad-5 is allelic to clk-2, and cloning of the rad-5/ clk-2 gene revealed that it encodes a protein homologous to S. cerevisiae Tel2 (42,43). The rad-5/clk-2 mutant is also sensitive to HU treatment and is defective in the DNA replication checkpoint (41).…”
mentioning
confidence: 99%
“…For example, S. cerevisiae Tel2p works in the same telomere maintenance pathway as Tel1p (Runge and Zakian 1996) and seems to bind to telomeric DNA (Kota and Runge 1998). Although a role of Tel2p in the DDR has not yet been described, its human counterpart controls sensitivity to DNA damaging agents whereas its C. elegans ortholog influences telomere length, the S-phase checkpoint, and controls life span and biological rhythms (Ahmed et al 2001;Benard et al 2001;Lim et al 2001;Jiang et al 2003).…”
Section: Dna-damage Checkpoint Proteins and Telomeresmentioning
confidence: 99%